Role of hormonal treatment in the management of prostate cancer - Senkus-Konefka, Elżbieta; Jassem, Jacek; Wełnicka-Jaśkiewicz, Marzena (Contemporary Oncology/Współczesna Onkologia, 2003)
Prostate cancer is one of the most common malignancies among men. Hormonal therapy is one of the essential treatment modalities of this malignancy. In previously untreated patients it allows for achieving 80–90% responses lasting from 12 to over 30 months. Hormonal manipulations in prostate cancer act via androgen deprivation, thus inhibiting cancer cell growth and tumor regression. Such an effect can be achieved either by inhibiting the production of androgens (by surgical or medical castration or by inhibition of adrenal androgen production), by the use of androgen receptor antagonists or by the use of estrogens. To improve treatment efficacy, a combined use of hormonal drugs of diverse mechanisms of action is proposed, although the value of such a therapy in most clinical situations was not confirmed in randomized studies. Some clinical effect can be also achieved due to the effect of withdrawal of antiandrogens. A number of randomized studies confirmed the activity of hormonal treatment initially in the management of an advanced disease, and recently also in combination with local modelities. The early application of hormonal treatment was demonstrated to prolong progression-free interval, decrease the risk of tumor-related complications and possibly increase the overall survival. Current research is focusing not only on improving anti-cancer efficacy, but also on decreasing treatment toxicity and improvement of patients’ quality of life. Attempts to improve treatment tolerability are also made with the use of intermittent androgen deprivation.